1–6 GHz ultrawideband 4 W single‐ended GaN power amplifier. Issue 1 (25th November 2013) - Giofre, Rocco; Colantonio, Paolo; Giannini, Franco
ABSTRACT In this contribution, the design approach and the experimental results of an ultrawideband power amplifier in GaN technology is presented. The amplifier is designed in a single‐ended configuration by using a 0.5 μm GaN HEMT with 1 mm gate periphery. The realized amplifier shows an efficiency higher than 40% with an output power greater than 36 dBm and an associated gain around 10 dB from 1 to 6 GHz. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:215–217, 2014